2021
DOI: 10.1002/ctm2.560
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation role of LH on porcine primordial germ cell‐like cells (pPGCLCs) through ceRNA network construction

Abstract: Background The transdifferentiation of skin‐derived stem cells (SDSCs) into primordial germ cell‐like cells (PGCLCs) is one of the major breakthroughs in the field of stem cells research in recent years. This technology provides a new theoretical basis for the treatment of human infertility. However, the transdifferentiation efficiency of SDSCs to PGCLCs is very low, and scientists are still exploring ways to improve this efficiency or promote the proliferation of PGCLCs. This study aims to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…Knowledge about how PGCs are induced comes largely from studies in model mammals, including nonhuman primates, 86,87,[89][90][91][92][93][94][95] mice, 12,83,85,[96][97][98][99][100][101][102][103][104][105][106][107][108] and pigs. [109][110][111][112][113][114][115][116][117][118] Studies in the other group of model organisms, including chicken, [119][120][121][122][123][124][125][126] zebrafish, 63,64,66,67,127 medaka, [128][129]…”
Section: Regulation Of Hpgc Specificationmentioning
confidence: 99%
“…Knowledge about how PGCs are induced comes largely from studies in model mammals, including nonhuman primates, 86,87,[89][90][91][92][93][94][95] mice, 12,83,85,[96][97][98][99][100][101][102][103][104][105][106][107][108] and pigs. [109][110][111][112][113][114][115][116][117][118] Studies in the other group of model organisms, including chicken, [119][120][121][122][123][124][125][126] zebrafish, 63,64,66,67,127 medaka, [128][129]…”
Section: Regulation Of Hpgc Specificationmentioning
confidence: 99%
“…Although the developmental trajectory of the porcine PGCLCs mainly follows that of mouse, the induction of SOX17 expression found in porcine PGCLCs also indicates the similarity to that of human ( Wang et al, 2016 ). Several studies reported the expansion protocol for porcine PGCLCs ( Yan et al, 2019 ; Zhang et al, 2021a ). The porcine PGCLC proliferation can be promoted by RA, which increases the proportion of cells in the S and G2/M phase but reduce those in the G0/G1 phase ( Yan et al, 2019 ).…”
Section: Current Progress On In-vitro Differentiat...mentioning
confidence: 99%
“…Luteinising hormone (LH) can enhance PGCLC proliferation by increasing the expression of proliferation-related genes ( CDK1, CDK2 ) and reducing that of the apoptosis genes ( P21 , P53 ). It is also shown that LH promotes the expansion during differentiation through the Hippo pathway ( Zhang et al, 2021a ).…”
Section: Current Progress On In-vitro Differentiat...mentioning
confidence: 99%
“…On the other hand, research on optimizing cell culture medium was carried out since Niels Geijsen et al derived PGCs from ESCs by culturing with leukemia inhibitory factor in 2004 [ 201 ]. Until now, there have been several biochemical agents used in inducing PGCLCs differentiation in vitro, such as retinoic acid promoting the differentiation of PGCLCs from skin-derived stem cells [ 202 ]; retinoic acid combined with CHIR99021 promoting the differentiation of PGCLCs from human ESCs [ 203 ]; luteinizing hormone regulating the proliferation of porcine PGCLCs through ceRNA network [ 204 ]. Furthermore, recent research has identified the role of epigenetic modification in the differentiation of PGCLCs in vitro.…”
Section: Current Knowledge Of Pgcsmentioning
confidence: 99%